2020
DOI: 10.1136/jech-2020-214181
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial determinants predicting long-term sickness absence: a register-based cohort study

Abstract: BackgroundThis study assessed the psychosocial determinants as explanatory variables for the length of the work disability period. The aim was to estimate the predictive value of a selected set of psychosocial determinants from the Quickscan questionnaire for the length of the sick leave period. A comparison was also made with the most common biomedical determinant: diagnosis.MethodsIn a cohort study of 4 981 insured Belgian patients, the length of the sick leave was calculated using Kaplan–Meier. Predictive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…This is consistent with other studies showing that poor SRH is a marker for increased length of sick leave [ 54 ] but also for increased risk of permanent work disability [ 55 ]. Similar findings were reported in a Belgian cohort study [ 56 ], based on a biopsychosocial model, that examined psychosocial factors predicting long-term sick leave. Fourteen factors showed significance for the length of sick leave, and among these were the patient’s perception of health.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with other studies showing that poor SRH is a marker for increased length of sick leave [ 54 ] but also for increased risk of permanent work disability [ 55 ]. Similar findings were reported in a Belgian cohort study [ 56 ], based on a biopsychosocial model, that examined psychosocial factors predicting long-term sick leave. Fourteen factors showed significance for the length of sick leave, and among these were the patient’s perception of health.…”
Section: Discussionsupporting
confidence: 87%
“…Fourteen factors showed significance for the length of sick leave, and among these were the patient’s perception of health. With better perceived health, the sick-leave period was shorter [ 56 ]. A large Dutch cohort study [ 31 ] had a similar purpose of investigating factors predicting long-term sick leave but was based on a broader multivariate risk model.…”
Section: Discussionmentioning
confidence: 99%
“…L iterature reviews and individual studies have investigated the role of self-reported health and diagnosed health problems as reasons for sickness absence (SA) in general and for long-term sickness absence (LTSA) in particular. [1][2][3][4][5] Similarly, the role of ill health as cause or consequence of sickness presence (SP) has been studied frequently. [6][7][8][9][10][11][12][13][14] Studies have also compared consequences of SA and SP on health, well-being, and work ability.…”
mentioning
confidence: 99%
“…Previous work exploring the prediction of sickness absence has focussed on speci c predictors and conditions (15)(16)(17)(18)(19). The most widely used model to predict work absence is the Orebro Musculoskeletal Pain Questionnaire, and its short version (20,21), both of which were developed in populations with back pain only.…”
Section: Introductionmentioning
confidence: 99%